Prevalence of infectious diseases on dairy farms classified on the basis of their biosecurity score - Perillo Laura; Cascone Giuseppe; Antoci Francesco; Piccione Giuseppe; Giannetto Claudia; Salonia Rosario; Salina Felice; Giudice Elisabetta; Monteverde Vincenzo; Licitra Francesca (Journal of Veterinary Research, 2022)
The aim of the study was to investigate the relationship between biosecurity as scored on the Italian National Animal Welfare Reference Centre (Centro di Referenza Nazionale per il Benessere Animale – CReNBA) checklist and the prevalence of Mycobacterium avium subsp. paratuberculosis, Chlamydophila abortus and Neospora caninum on dairy farms located in Ragusa, Italy.